"PLEASE DENY THESE MANIFESTLY FALSE REPORTS": OTTOMAN DIPLOMATS AND THE PRESS IN BELGIUM (1850–1914). (7th April 2016) - Alloul, Houssine; Markey, Roel
Abstract: Similar to ruling elites in Western Europe, the Ottomans were preoccupied with foreign "public opinion" regarding their state. Historians have devoted attention to Ottoman state efforts at image building abroad and, to a lesser degree, related attempts to influence the European mass press. Yet, an in-depth study of this subject is lacking. This article turns to one of the prime, though largely neglected, actors in Ottoman foreign policy making: the sultan's diplomats. Through a case study of Ottoman envoys to Belgium, it demonstrates how foreign "press management" evolved and was adapted to shifting domestic and international political circumstances. Increasingly systematic attempts to influence Belgian newspapers can be discerned from the reign of Abdülhamid II onward. Brokers between Istanbul and "liberal" Belgium's thriving newspaper business, Ottoman diplomats proved essential to this development. Ultimately, however, Ottoman efforts to counter Belgian (and European) news coverage of the empire had little impact and occasionally even worked counterproductively, generating the very Orientalist images they aimed to combat in the first place.